Accounting Standards Harmonization and Financial Statement Comparability: Evidence from Transnational Information Transfer - WANG, CLARE (Journal of Accounting Research, 2014)
ABSTRACT This paper investigates whether accounting standards harmonization enhances the comparability of financial information across countries. I hypothesize that a firm yet to announce earnings reacts more strongly to the earnings announcement of a foreign firm when both report under the same rather than different accounting standards. My analysis of abnormal price reactions for a global sample of firms supports the prediction. Next, in an attempt to control for the underlying economic comparability and the effects of changes in reporting quality, I use a difference‐in‐differences design around the mandatory introduction of International Financial Reporting Standards. I find that mandatory adopters experience a significant increase in market reactions to the release of earnings by voluntary adopters compared to the period preceding mandatory adoption. This increase is not observed for nonadopters. Taken together, the results show that accounting standards harmonization facilitates transnational information transfer and suggest financial statement comparability as a direct mechanism.